The correlation between intracranial atherosclerosis and white matter hyperintensities in cerebral small vessel disease: a high-resolution magnetic resonance imaging study - Zhang, Gui-Song; Bu, Wei; Meng, Ling-Hui; Li, Wen-Jun; Dong, Yu-Juan; Cao, Xiao-Yun; Gao, Qi; Zhang, Xuan-Ye; Ren, Hui-Ling (Frontiers in Neurology, 2025)
ObjectiveRecent studies have indicated a close relationship between intracranial arterial stenosis and white matter hyperintensities (WMHs), but few have reported on the correlation between the characteristics of intracranial arterial wall plaques and WMHs. The aim of this study was to comprehensively assess the correlation between intracranial atherosclerosis plaques and WMHs using 3.0T high-resolution magnetic resonance imaging (HR-MRI).Patients and methodsNinety-two ischemic stroke patients with middle cerebral artery (MCA) stenosis <50% on cranial magnetic resonance angiography (MRA) underwent conventional MRI and HR-MRI examinations. T2-weighted fluid-attenuated inversion recovery (T2-FLAIR) images were processed using 2D VBNeT automatic segmentation technology to segment WMH volume. HR-MRI images were analyzed using ImageJ software to evaluate the luminal area, outer wall area, plaque distribution, luminal stenosis rate, remodeling patterns, and other plaque parameters at the stenosis site and reference points of the MCA M1 segment. The correlation between the presence of plaques, plaque distribution, luminal stenosis rate, T1 hyperintensity, remodeling patterns, remodeling ratio (RR), eccentric plaques, and plaque burden with the volume of cerebral WMHs was analyzed.ResultsCompared with the no-plaque group, the plaque group had significantly higher age, male ratio, total WMH volume, periventricular WMH (PVWMH) volume, deep WMH (DWMH) volume, and juxtacortical WMH (JCWMH) volume (all p < 0.05). The Kruskal-Wallis H test showed that patients with plaques on the superior and dorsal sides of the MCA M1 segment had higher levels of total WMH volume, PVWMH volume, DWMH volume, and JCWMH volume than patients with plaques on the inferior and ventral sides (all p < 0.05). Age, diabetes, previous stroke events, plaque distribution, positive remodeling, eccentric plaques, and RR were positively correlated with total WMH volume, PVWMH volume, and JCWMH volume (all p < 0.05). The presence of plaques, plaque distribution, and positive remodeling were independent risk factors for total WMH volume (all p < 0.05).ConclusionThe presence of intracranial atherosclerotic plaques, plaque distribution, and positive remodeling are closely associated with increased cerebral WMHs burden in patients with ischemic stroke, which further supports the relationship between large artery atherosclerosis and CSVD.